Rest-activity rhythms in small scale homelike care and traditional care for residents with dementia - Kok, Jeroen S. (BMC Geriatr, 2017)
BACKGROUND: An enriched environment for residents with dementia may have a positive effect on the rest-activity rhythm. A small scaled homelike special care unit might be such an enriched environment. The present study shows whether the rest-activity rhythm of residents with moderate to severe dementia responds positively to a transfer from a regular Special Care Unit (SCU) to a small scaled homelike SCU. METHODS: Initially, a group of 145 residents living in a regular SCU participated. Out of this group, 77 residents moved to a small scaled homelike SCU. This group was compared to the group of 68 residents that remained at the regular SCU. Rest-activity rhythm was assessed by means of actigraphy and observation scales before and after relocation. RESULTS: No significant main effects nor significant interaction effects in intradaily and interdaily activity were found for the data of 38 residents in the small scaled homelike SCU and 20 residents of the regular SCU. The effect sizes, however, ranged from small to large. CONCLUSIONS: Considering the effect sizes, a new study with a larger number of participants is necessary before firm conclusions can be drawn. TRIAL REGISTRATION: Current Controlled Trials ISRCTN11151241. registration date: 21–06-2017. Retrospectively registered.